Structure–Activity Relationship Studies of Pyridine-Based Ligands and Identification of a Fluorinated Derivative for Positron Emission Tomography Imaging of Cannabinoid Type 2 Receptors - Haider, Achi; Kretz, Julian; Gobbi, Luca; Ahmed, Hazem; Atz, Kenneth; Bürkler, Markus; Bartelmus, Christian; Fingerle, Jürgen; Guba, Wolfgang; Ullmer, Christoph; Honer, Michael; Knuesel, Irene; et al. (Journal of medicinal chemistry, 2019)
The cannabinoid type 2 (CB2) receptor has emerged as a valuable target for therapy and imaging of immune-mediated pathologies. With the aim to find a suitable radiofluorinated analogue of the previously reported CB2 positron emission tomography (PET) radioligand [11C]RSR-056, 38 fluorinated derivatives were synthesized and tested by in vitro binding assays. With a K i (hCB2) of 6 nM and a selectivity factor of nearly 700 over cannabinoid type 1 receptors, target compound 3 exhibited optimal in vitro properties and was selected for evaluation as a PET radioligand. [18F]3 was obtained in an average radiochemical yield of 11 ± 4% and molar activities between 33 and 114 GBq/μmol. Specific binding of [18F]3 to CB2 was demonstrated by in vitro autoradiography and in vivo PET experiments using the CB2 ligand GW-405 833. Metabolite analysis revealed only intact [18F]3 in the rat brain. [18F]3 detected CB2 upregulation in human amyotrophic lateral sclerosis spinal cord tissue and may thus become a candidate for diagnostic use in humans.